Materials chemistry - Fahlman, Bradley D. (Springer, 2011)
The 2nd edition of Materials Chemistry builds on the strengths that were recognized by a 2008 Textbook Excellence Award from the Text and Academic Authors Association (TAA). Materials Chemistry addresses inorganic-, organic-, and nano-based materials from a structure vs. property treatment, providing a suitable breadth and depth coverage of the rapidly evolving materials field. The 2nd edition continues to offer innovative coverage and practical perspective throughout. After briefly defining materials chemistry and its history, seven chapters discuss solid-state chemistry, metals, semiconducting materials, organic soft materials, nanomaterials, and materials characterization. All chapters have been thoroughly updated and expanded with, for example, new sections on ?soft lithographic? patterning, click chemistry polymerization, nanotoxicity, graphene, as well as many biomaterials applications. The polymer and soft materials chapter represents the largest expansion for the 2nd edition. Each chapter concludes with a section that describes important materials applications, and an updated list of thought-provoking questions. The appendices have also been updated with additional laboratory modules for materials synthesis and a comprehensive timeline of major materials developments. Appropriate for junior/senior undergraduate students, as well as first-year graduate students in chemistry, physics, or engineering. Materials Chemistry may also serve as a reference to industrial researchers. The author chose depth over breadth, resulting in deep, detailed prose. The strenghts of this book are its illustrations and color graphics, as well as up-to-date references and examples. Choice Reviews Online, 2008 on Materials Chemistry 1st edition.